The Impact of Digital Technology Implementation on the Efficiency of Educational Administration - Antik Pujihastuti; Irianto M.Ali; Lu'luil Maknun (Gateway for Understanding Research in Education, 2025)
The advancement of digital technology profoundly influences educational administration by enhancing efficiency and service quality. This study aims to examine the impact of digital technology implementation on administrative effectiveness across various educational institutions in Indonesia. Employing a qualitative descriptive methodology supported by extensive literature review, data were collected through interviews, observations, and institutional records from primary schools, Islamic junior high schools, and universities. The findings reveal significant reductions in processing time (up to 66%), operational costs (up to 75%), and data errors, alongside increased transparency and accessibility. Despite these benefits, challenges such as infrastructure limitations and resistance to cultural change remain. The study concludes that digitalization is crucial for modernizing educational administration, requiring strategic investment in infrastructure and human resource development. This research underscores the imperative for educational institutions to embrace digital transformation as a foundation for efficient, transparent, and accountable governance in the 4.0 era.